Sex Differences in Secularity in Iran - Kevin McCaffree; Anondah Saide; Farinaz Basmechi (Secularism and Nonreligion)
The qualitative study of declining religious influence in society, or secularization, has been conducted almost exclusively in Western societies. As a result, our theoretical understanding of the social psychological and institutional mechanisms driving sex differences in secularity are over-reliant on a relatively small subset of societies. In this study, one of the first of its kind, we examine the process of secularization amongst a sample of men and women raised Muslim in Iran. We draw from 21 in-depth interviews (52% female) to identify three themes central to individuals’ uncertainty about religion. In doing so, we uncover several unexpected findings with little precedence in Western secularization research. Given the dearth of research on sex differences in secularization amongst people raised Muslim in Muslim-majority countries, our results provide new and novel directions for scholars to pursue in future work.